Balancing Economic Sustainability with Densification: A Case Study of Dhaka. (Global Journal of Human-Social Science, 2023)
Economically sustainable urban residential neighborhoods are characterized by adequate provision of physical infrastructure including transport facilities and utility services The built urban fabric of residential areas of Dhaka has been undergoing densification operation over the past decades without considering the physical infrastructure capacity of these areas in terms of accessibility and provision of transportation and utility services This intervention eventually exerted pressure on the existing infrastructure and caused negative externalities like traffic congestion pollution and water clogging Thus this paper aims to investigate the impact of densification on residential areas of Dhaka through the lens of economic sustainability Seven residential areas from Old and New Dhaka that underwent various degrees of densification were selected as the study areas Primary data was collected through a random sampling household questionnaire survey fieldwork and informal qualitative interviews with the residents and officials Various published literature newspaper articles plans and reports from government archives Capital Development Authority RAJUK Dhaka South City Corporation DSCC and Dhaka North City Corporation DNCC provided the secondary data The analysis is carried out in two parts In the first part the impact of densification on accessibility to transportation facilities and utility services is analyzed in terms of availability of the services distance to the bus stops average travel time modal choice and residents satisfaction level The second part explores the relationship between density and aspects of economic sustainability through Pearson s correlation test The findings revealed that public transportation is more accessible in lower-density areas than the higher-density residential areas owing to the road network pattern
Keywords: urban densification; economic sustainability; sustainable transportation; utility services; infrastructure; public transport